Pengaruh Organizational Learning Culture terhadap Employee Outcomes pada Direktorat Jendral Pajak - Adesius Kevin Gregory; Indra Adithya Wibisana Irawan; Justine Tanuwijaya (Universitas Batanghari, 2022)
This study aims to determine the effect of organizational learning culture on employee outcomes at the Directorate General of Taxes. This research is a type of quantitative research. The primary data source of this research was obtained through the results of a questionnaire. Furthermore, the secondary data of this research is carried out through previous research studies in the form of journals. Methods of data collection through observation techniques, questionnaires and documentation. Furthermore, the analysis of this research is divided into validity and reliability tests of 30 respondents. Analysis with panel data consisting of 3 (three) research estimation methods, one of which must be chosen, namely Common Effect (CE), Fixed Effect (FE) and Random Effect (RE). The results show that organizational learning culture has a positive and significant effect on employees. outcomes.